What Drives Belief in Vaccination Conspiracy Theories in Germany? - Jensen, Eric Allen; Pfleger, Axel; Herbig, Lisa; Wagoner, Brady; Lorenz, Lars; Watzlawik, Meike (Frontiers in Communication, 2021)
In the midst of a pandemic, the efficacy of official measures to mitigate the COVID-19 crisis largely depends on public attitudes towards them, where conspiracy beliefs represent potential threats to the efficacy of measures such as vaccination. Here, we present predictors and outcomes associated with a COVID-19 vaccination conspiracy belief. In a representative survey of Germany, sociodemographic predictors of this belief were found to include age, federal state, migration background and school leaving qualification. The study revealed correlations with trust in scientific and governmental information sources, respondents’ self-assessment of being informed about science, general conspiracy mindedness, the frequency of using Twitter and messaging apps, as well as willingness to voluntarily take the COVID-19 vaccine. Our results cohere with and build on the general literature on conspiracy mindedness and related factors. The findings provide an evidence base for more effective health and crisis communication in Germany and beyond.